2004
DOI: 10.3171/jns.2004.101.3.0402
|View full text |Cite
|
Sign up to set email alerts
|

Shunt-dependent hydrocephalus after rupture of intracranial aneurysms: a prospective study of the influence of treatment modality

Abstract: Shunt-dependent hydrocephalus was comparable in the two treatment groups, even in patients with better clinical and radiological grades on admission. Only patients in the endovascular therapy group who had experienced IVH showed a higher likelihood of shunt-dependent hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
99
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 43 publications
(41 reference statements)
7
99
2
1
Order By: Relevance
“…Also, the influence of the quantity of blood in the subarachnoid space was supported by results from many other studies 7,8,12,18) . Our results showed a total rate of SDHC of 19.7%, which was consistent with results from other series found in the literature 4,5,8,16) . Based on our data, 0% of shunttreated patients were in FG 1, with 11.7% in FG 2, 51% in FG 3, and 37.3% in FG 4.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Also, the influence of the quantity of blood in the subarachnoid space was supported by results from many other studies 7,8,12,18) . Our results showed a total rate of SDHC of 19.7%, which was consistent with results from other series found in the literature 4,5,8,16) . Based on our data, 0% of shunttreated patients were in FG 1, with 11.7% in FG 2, 51% in FG 3, and 37.3% in FG 4.…”
Section: Discussionsupporting
confidence: 83%
“…Several Risk of Shunt Dependent Hydrocephalus : Clipping vs. Coiling | KH Nam, et al studies have compared the incidence of SDHC according to treatment modality. Most reports revealed that endovascular coiling could be attributed to an increased rate of SDHC 4,5,19) . However, Gruber et al 8) reported that the endovascular treatment group did not suffer SDHC more frequently than the surgical treatment group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such patients, CSF hydrodynamics are often only transiently disturbed and tend to normalize 40 to 50 days after SAH in most instances. 2 After this initial period of time, adequate shunt function may not be an important factor in many patients with SAH.…”
mentioning
confidence: 99%